Pemikiran Filosof Al-Farabi dan Ibnu Sina - Herman, Muhammad Akbar; Amri, Muhammad; Santalia, Indo (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The aim of this research is to understand the basic concepts of al-Farabi's thinking and the basic concepts of Ibn Sina's thinking. The results of this research show: 1) Al-Farabi or also known by his full name Abu Nasir Muhammad bin al-Farakh al-Farabi, was a scientist, philosopher and Islamic jurist who came from Farab, Kazakhstan. He was born in 870 AD in Wasij, a village near Farabi. Al-Farabi is known as one of the leading Muslim scholars of that time and is considered the second teacher of philosophy after Aristotle. The basic concepts of Al-Farabi's thoughts are God and His Attributes, Emanative Creation of Nature, Philosophy of the Soul, Philosophy of Prophethood and Life After Death; 2) Ibn Sina was born in 980 in Afshana, near Bukhara in Central Asia (now Uzbekistan). Ibn Sina was known as a child prodigy because he was able to read the Koran at the age of 10. In fact, he had sufficiently mastered contemporary medical knowledge and was able to put it into practice at the age of 16. When he was a teenager, he learned basic reasoning from a teacher, and then studied the thoughts of Hellenistic era philosophers autodidactically. The basic concepts of Ibn Sina's thought are obligatory al-wujud (which must exist) and mukmin al-wujud (which may exist), Qadim (something that did not exist in the beginning) and Muhdas (something that is created/created), the Theory of Emanation and God, Reason , Soul, and Body.